Hydrological, Hydraulic, and Topographic Analysis and Cost Estimation for Flood Control Design in Penajam Paser Utara Regency - Purwanto, Purwanto (JSE Journal of Science and Engineering, 2025)
Penajam Paser Utara Regency in East Kalimantan Province faces a high risk of flooding due to inadequate drainage channel capacity, irregular bed slopes, and sedimentation that reduces channel cross-sections. Increased runoff caused by land-use changes has exacerbated flooding, particularly in densely populated residential areas. This study aims to prepare a comprehensive Survey, Investigation, and Design (SID) document for flood control as a basis for planning measurable drainage infrastructure development. The research methods include collecting rainfall data from the Waru Station, calculating design flood discharges using the Gumbel Type I, Log-Pearson Type III, Log-Normal, and Frechet distributions, conducting hydraulic analyses using the Strickler and Manning formulas, simulating channel profiles with the Hydrologic Engineering Center – River Analysis System (HEC-RAS) software, and performing topographic surveys to determine channel cross-sections and benchmark elevations. The results indicate that the highest design flood discharge occurs in Waru Village, reaching 4.751 cubic meters per second for a 25-year return period. The hydraulic simulations support the need for channel normalization, slope adjustments, dimensional standardization, construction of polders, flap gates, and the operation of water pumps. The study concludes that drainage development should be implemented in stages with community participation in maintenance and pump operation funding.